An adult case with shigellosis-associated encephalopathy. (18th January 2018) - Schuster, Heleen Joséphine; Gompelman, Michelle; Ang, Wim; Kooter, Albertus Jozef
Abstract : A 45-year-old man was presented at the emergency department with altered neurological status and a 1-day history of diarrhoea and fever. The patient's sexual history revealed multiple male partners. As bacterial meningitis or viral encephalitis was suspected, treatment was started accordingly. Cerebrospinal fluid investigations only showed a slight increase of leucocytes, and microbiological studies remained negative. Stool culture revealed Shigella flexneri, after which Shigella- associated encephalopathy was suspected. The patient recovered quickly with antibiotic treatment. The incidence of Shigella infections in the Western world is rising due to sexual transmission among men who have sex with men. Shigella -induced encephalopathy is a notorious complication among children with a severe form known as the Ekiri syndrome, though rarely seen in adults. This is the second report of encephalopathy in an adult with S. flexneri enteric infection.